2015
DOI: 10.1186/s12889-015-2649-6
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence, risk factors, and screening measure for prediabetes and diabetes among Emirati overweight/obese children and adolescents

Abstract: BackgroundThe aim of the study was to estimate the prevalence of prediabetes and type 2 diabetes (T2D) among overweight/obese children and adolescents using different diagnostic/screening methods in comparison.MethodsWe recruited overweight/obese Emirati students; grade 6–12 (age 11–17 years) from 16 government schools in Sharjah (UAE). Anthropometric, demographic, and clinical history data was measured by standard methods. Body mass index (BMI) was categorized according to BMI percentile charts for age and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
69
4
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(92 citation statements)
references
References 37 publications
6
69
4
2
Order By: Relevance
“…Similar to previous published prevalence rates of type 2 diabetes, the present study found a predominance of females in these categories . The prevalence of prediabetes has been investigated in various countries across the world, including Mexico (1.5%), UAE (5.4%) and China (0.28%) . The studies emerging from the United States and Canada focus on adolescents who have been diagnosed with diabetes or present findings that estimate the prevalence of prediabetes and/or undiagnosed diabetes .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similar to previous published prevalence rates of type 2 diabetes, the present study found a predominance of females in these categories . The prevalence of prediabetes has been investigated in various countries across the world, including Mexico (1.5%), UAE (5.4%) and China (0.28%) . The studies emerging from the United States and Canada focus on adolescents who have been diagnosed with diabetes or present findings that estimate the prevalence of prediabetes and/or undiagnosed diabetes .…”
Section: Discussionsupporting
confidence: 87%
“…China (0.28%). [24][25][26] The studies emerging from the United States diabetes or present findings that estimate the prevalence of prediabetes and/or undiagnosed diabetes. 8,[27][28][29] In the present study, community-based screening was undertaken to determine the number of Canadian adolescents who were in the "at risk" or prediabetes and type 2 diabetes blood glucose range.…”
Section: Discussionmentioning
confidence: 99%
“…Regionally, among Saudi children and adolescents aged ≤18 years, prediabetes prevalence, defined based on ADA's IFG diagnostic criteria, was estimated to be 6.12% . In contrast, among obese/overweight Emirati children and adolescents (aged 11‐17 years), prediabetes prevalence was estimated to be 21.9% according to the HbA1c ADA criteria . As for international studies, prediabetes prevalence among the general population of children and adolescents in the United States (HbA1c ADA : 17.8%) and Taiwan (IFG ADA : 22.0%) were less than our estimated prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…Another important risk factor is family history. In a study conducted by Elham Al Almiri and co‐authors, more than half of prediabetic patients and all with T2D had a first‐degree relative with T2D . Prediabetes (20%) and diabetes (70%) participants had also raised triglyceride levels …”
Section: Overweight and Obesity In T2dmentioning
confidence: 98%